A prospective randomized study to compare dexmedetomidine and dexamethasone as an adjunct to bupivacaine in transversus abdominis plane block for post-operative analgesia in caesarean delivery - Thakur, Jitender; Gupta, Bharti; Gupta, Amit; Verma, Ravinder Kumar; Verma, Anita; Shah, Payal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Caesarean section is most frequently performed surgery worldwide. Patients experience moderate to severe pain in the first 48 hours post-operatively. Aim of this study was to evaluate the efficacy of dexmedetomidine and dexamethasone as an adjunct to bupivacaine in ultrasound guided TAP block for postoperative analgesia in patients of caesarean section. Methods: A total 120 ASA I and II patients undergoing elective and emergency caesarean section under subarachnoid block were randomly divided into three groups B, BDM, BDX to receive bupivacaine alone or dexmedetomidine or dexamethasone as an adjunct to bupivacaine in ultrasound guided TAP block. Postoperatively, the patients were evaluated for pain level at rest and on movement with a 10 cm visual analog scale (VAS) pain score (0 = no pain and 10 = worst pain), time to demand of first analgesic request, number of analgesic requirements, nausea or vomiting, sedation and patient satisfaction at 0 hours and at 2, 4, 6, 12, 18, and 24 hours. Results: VAS score was significantly higher in group B in comparison to BDM and BDX, and higher in BDX in comparison to group BDM. Mean duration of analgesia was significantly higher in group BDM in comparison to group B and BDX. Total number of rescue analgesic demands were significantly lower in group BDM in comparison to group B and BDX. Sedation score and satisfaction score was higher in group BDM as compared to group B and BDX. Conclusions: Addition of dexmedetomidine and dexamethasone as an adjunct to bupivacaine reduces postoperative pain, prolongs analgesia, decreases demand for additional analgesics and provides better maternal satisfaction as compared to plain bupivacaine group in TAP block in patients undergoing caesarean section under subarachnoid block. Among dexmedetomidine and dexamethasone, dexmedetomidine had prolonged analgesia as compared to dexamethasone group.